2022
DOI: 10.31292/mj.v1i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Ulayat Land and Agrarian Reform Policy in West Sumatra

Abstract: One of the objects of Agrarian Reform in West Sumatra is the Ulayat Land. The practice is carried out by changing the status of Ulayat Land to state land through the mechanism of release by Niniak Mamak. Ulayat Land is a plot of heritage land and its natural resources obtained from generations as regulated by local governments both in designation and utilization. This study aims to explain why Ulayat Land is used as a Land Object of Agrarian Reform (TORA) in West Sumatra and why the mechanism of giving is indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Penelitian terkait dengan reforma agraria fokus pada kawasan hutan dikaji dengan berbagai perspektif (Ekawati at al., 2019;Manik at al., 2021;Khanifa at al., 2021;Dempo at al., 2021;Junarto & Djurdjani 2020;Kurniawati et al, 2019;Salim et al, 2021). Penelitian terkait reforma pada tanah ulayat masyarakat hukum adat (Wardhana, 2020;Wahyuni, 2021;Ihsan & Salim, 2022;Chandra, 2022;). Pelaksanaan reforma agraria tidak hanya memberikan efek pada sektor ekonomi saja, melainkan juga memberikan efek sosial pada kehidupan masyarakat suatu daerah (Tarfi & Amri, 2021).…”
Section: A Pendahuluanunclassified
“…Penelitian terkait dengan reforma agraria fokus pada kawasan hutan dikaji dengan berbagai perspektif (Ekawati at al., 2019;Manik at al., 2021;Khanifa at al., 2021;Dempo at al., 2021;Junarto & Djurdjani 2020;Kurniawati et al, 2019;Salim et al, 2021). Penelitian terkait reforma pada tanah ulayat masyarakat hukum adat (Wardhana, 2020;Wahyuni, 2021;Ihsan & Salim, 2022;Chandra, 2022;). Pelaksanaan reforma agraria tidak hanya memberikan efek pada sektor ekonomi saja, melainkan juga memberikan efek sosial pada kehidupan masyarakat suatu daerah (Tarfi & Amri, 2021).…”
Section: A Pendahuluanunclassified
“…In this case, of course, sole proprietorship in the hands of the king is not a representation of ideal land management. As mentioned by Tahir (2002), feudalism is the cause of poverty that the way out of this system must be done through agrarian reform, but not agrarian reform by distributing land into property rights (Ihsan & Salim, 2022), but redistribution of fair land use to create custom-based welfare/local wisdom. Agrarian reform is an effort to remove feudalism by transforming the democratic system into a more modern one to achieve economic and political equality (Goldman, 2015).…”
Section: Redistribution Of Welfare Based On Local Wisdommentioning
confidence: 99%
“…Studies related to the redistribution of customary land are something that is rarely found, because so far the problem of customary land is very complicated, so there are rarely studies related to the redistribution of customary land. Based on these limitations, there was a study of customary land redistribution conducted by Ihsan and Salim (2022) which raised the issue of redistribution of customary land of the Domo Tribe indigenous community in Dharmasraya Regency, West Sumatra.…”
Section: A Introductionmentioning
confidence: 99%